Netralitas dan Keseimbangan Pemberitaan Surat Kabar Daerah dalam Pilkada DIY 2005 Tahap Kampanye Terbuka (Analisis Isi Harian Kedaulatan Rakyat dan Kompas Yogya) - Anang Hermawan (Jurnal Komunikasi)
This research analyzed neutrality and balance of two local newspapers, especially for election reporting during public campaign period (June 9-22,2005) in three cities of Yogyakarta Special Province (Bantul, Sleman, Gunungkidul). The research used quantitative content analysis methods, and the objects of the research were selected news in Kedaulatan Rakyat and Kompas Yogya. The neutrality aspect was measured by dramatization that indicated from the existence of personalization, emotionalism, hyperbola, and irrelevance details. Then, the balance aspect was measured by presentation in some aspects of cover both sides principle, including avoidance of slant and source bias. This research found the lack of neutrality presentation and balance dimension. The highest aspect contributed by hyperbolic and irrelevance details. On the other hand, the imbalance reports occurred by source bias, showed by high percentage of slant and domination of candidates supporter groups.